Monetary policy and bank distress: an integrated micro-macro approach - Ferre De Graeve; Thomas Kick (Deutsche Bundesbank, 2008)
Evidence on the interdependency between monetary policy and the state of the banking system is scarce. We suggest an integrated micro-macro approach with two core virtues. First, we measure the probability of bank distress directly at the bank level. Second, we integrate a microeconomic hazard model for bank distress and a standard macroeconomic model. The advantage of this approach is to incorporate micro information, to allow for non-linearities and to permit general feedback effects between bank distress and the real economy. We base the analysis on German bank and macro data between 1995 and 2004. Our results confirm the existence of a relationship between monetary policy and bank distress. A monetary contraction increases the mean probability of distress. This effect disappears when neglecting micro effects, underlining the crucial importance of the former. Distress responses are economically most significant for weak distress events and at times when capitalization is low.
Keywords: E58; G21; E52; E42; G28; 330; Stress testing; bank distress; monetary policy; Geldpolitik; Schock; Transmissionsmechanismus; Bankrisiko; Bankenliquidität; Deutschland